DESCRIPTION OF BIOSECURITY IMPLEMENTATION ON PIG FARMS IN KERTA VILLAGE, PAYANGAN SUB-DISTRICT, GIANYAR DISTRICT - Ki Komang Desi Anggelia; I Wayan Masa Tenaya; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2025)
The threat of diseases that can hamper farm production follows the increasing demand for pig products in the global market. The purpose of this study was to determine how biosecurity is implemented on pig farms in Kerta Village, Payangan District, Gianyar Regency. In this study, a descriptive observational method was used, and data were collected through questionnaire-based interviews with 33 local pig farmers and the results were analyzed descriptively qualitatively using a Guttman scale. This study aims to be able to provide an overview of the l implementation of biosecurity implementation on farms. The picture of biosecurity implementation on pig farms in Kerta Village, Payangan District, Gianyar Regency, especially in the fattening phase of pigs shows poor implementation. The implementation of biosecurity should be done well on pig farms because it is very important to prevent the spread of disease and maintain animal health.